Preparation of a feasibility study for new nuclear power projects. (International Atomic Energy Agency, 2014)
A feasibility study represents an important step in the development of a new build nuclear power plant project. It is a complex but necessary step to determine whether a business opportunity is possible, practical and viable. Technical, economic, financial, regulatory, social and environmental aspects of a nuclear power plant programme need to be considered to allow authorities to make informed decisions regarding the possible implementation of the project. This publication assists Member States in developing a feasibility study for nuclear power projects and provides guidance to users who are planning to perform such a study, with consideration of both the technical and process areas. These guidelines condense the experience of individuals involved in previous feasibility study efforts and provide industry best practices in order to maximize the usefulness of any results.
Keywords: Nuclear power plants -- Planning.; Nuclear energy -- Economic aspects.; Nuclear energy -- Environmental aspects.; Nuclear energy -- Social aspects.; elektronické knihy; electronic books